Bias Controller of Mach–Zehnder Modulator for Electro-Optic Analog-to-Digital Converter - Shi, Shuxin; Yuan, Jun; Huang, Qin; Shi, Chongyu; Luo, Xin; Lu, Shan; Yuan, Pengfei; Yu, Hua; Yue, Qiuqin (Micromachines (Basel), 2019)
As one of the core devices for an electro-optic analog-to-digital converter (ADC), the Mach–Zehnder (MZ) modulator plays an important role, and the output stability of the MZ modulator has a decisive influence on the conversion accuracy of the ADC. This paper proposed a pilot tone-based method to stabilize the bias point of the modulator. This method could obtain the corresponding control voltage of the MZ modulator by adding a KHz-level dither tone to the bias end of the modulator and calculating the ratio of the first and second harmonic components. The experimental results showed that the output optical power of the modulator was stable at 3.2 dB when the bias point of the modulator was set at the orthogonal point. Moreover, the fluctuation range was not more than 0.15 dB, the first harmonic of the output signal was stable at 50.5 dB, and the fluctuation range was not more than 0.6 dB. The proposed bias controller based on the field programmable gate array (FPGA) and digital signal processing (DSP) can stabilize the modulator bias point at the orthogonal point and with a relatively high locking accuracy.